Quality in the formation of doctors in pedagogical sciences: graduates´ evaluation and proposals for improvement - Ortiz-Torres, Emilio Alberto (2018)
The formation of Doctors of Philosophy is an important issue in universities. Several researchers have studied the multiple aspects related to this topic in different social and cultural contexts with valuable contributions such as competences, professional skills needed for students to develop their thesis, difficulties in academic writing, scientific and social impact of the results obtained and  the role of tutors and their previous formation. The evaluation of the quality of this formation has always been implicit in all these considerations from the vision of the professors, but the criteria of the graduates have hardly been considered. This situation is prevalent in the case of the doctorates in pedagogical sciences developed in Cuba. Thus, the objective of this article was to evaluate the quality of the teaching process of graduates in pedagogical sciences based on their personal evaluation with the intention of enhancing it with the graduates´ improvement proposals. Several methodological scientific procedures were proposed to self- assess the graduates in order to obtain objective, valuable, truthful, and pertinent information to be used immediately in the process of continuous improvement that the doctoral education demands to improve its quality.